A157 INCIDENCE OF VENOUS THROMBOEMBOLIC EVENTS IN PATIENTS WITH ULCERTIVE COLITIS DURING HOSPITALIZED AND POST-DISCHARGE SETTINGS. (1st March 2018) - Israel, A; Murthy, S; Bollu, A; Parlow, S; McCurdy, J
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at increased risk of venous thromboembolism (VTE) events. Hospitalized patients carry a higher risk for VTE events and as such guidelines recommend thromboprophylaxis for all admitted IBD patients. Risk of VTE in the post-discharge setting has not been as well defined; therefore, it remains unknown if extended thromboprophylaxis is warranted. Aims: To compare the incidence of VTE events in patients with ulcerative colitis (UC) during hospitalized and post-discharge settings. Methods: A retrospective observational study was conducted on consecutive UC patients admitted to The Ottawa Hospital with a disease flare between April 1 2006 and April 30 2012. Symptomatic VTE events were assessed during hospitalization and up to 1-year post-discharge through chart review. Results: Of the 184 patients included, average length of stay was 12.3 days. Ninety four (51%) patients were male, with a median age of 41 years and 23% were current or ex-smokers. Thirty eight percent of all patients received prophylactic or full dose anticoagulation during admission. Overall 17 patients (9%) developed a VTE; 13 (7%) of inpatients and 4 (2%) of outpatients. The median time to diagnosis of outpatient VTE was 4 days (range 4–9 days). Of all VTE patients, 35% received thromboprophylaxis; 45% of inpatients and 25% of outpatients. Of all VTE patients, 82% received corticosteroids, 15% received biologics and 12% underwent colectomy during hospitalization. Of the patients who developed outpatient VTE, all were treated with corticosteroids and 1 (25%) with biologics. None of these patients underwent colectomy. Table 1 describes the individual outpatient VTE events. Conclusions: In this small retrospective study VTE events were rare in patients with UC following discharge from hospital. Future studies with larger sample sizes are required to confirm these findings and to identify predictors of high-risk patients who may benefit from extended thromboprophylaxis. Funding Agencies: None